Pedagogical Characteristics of Organizing the Student Community in the Organization and Management of Educational Work Processes in Higher Education Institutions - Dadagoziev, Muzaffar Rakhnomoyevich (International Journal on Integrated Education, 2023)
This article analyzes the pedagogical features of organizing the student team in the organization and management of educational work processes in higher education institutions.